The religious aspect in the lesson of cloning topic in Islamic organization-based high school - A L Alindra; A Widodo; T Rahman; Riandi Riandi (Pascasarjana Universitas Pendidikan Indonesia, 2021)
Several aspects of biology teaching affect teachers in carrying out their duties, such as their religious beliefs. This factor affects them in delivering lessons on controversial topics between science and religion. The cloning topic is one of the most controversial topics in terms of science and religion. Therefore, this study aimed to describe the religious aspect of cloning lessons in Islamic organizations-based school. A descriptive qualitative design was used to elaborate on three biology teachers by observing, documenting, and interviewing them. The observations were recorded with a video camera. Meanwhile, the interview with students, principals, and the teachers were used to triangulate the data, which were transcribed and descriptively analyzed. Therefore, the documentation was due to the gain in the lesson plan and school profile. The participants were three biology teachers of class XII in three high schools in South Tangerang, Banten Province, Indonesia. The results showed that the integration of religious values in the learning of cloning topics is not entirely determined by Islamic organizations, but the teachers' ability to understand and integrate the values in learning. This is a challenge for Islamic organization-based schools to evaluate the implementation of the school's vision and missions in the learning. Therefore, biology teachers need to be trained in Islamic schools to appropriately integrate the values of science and religion